Prenatal Birth Planning for Families of the Imperiled Newborn. Issue 3 (18th April 2013) - English, Nancy K.; Hessler, Karen L.
ABSTRACT Guidelines have not been established to address the needs of parents with imperiled newborns due to the infrequency of this obstetric situation. In this article we offer an approach to prenatal care planning for imperiled newborns and their families. Use of an interdisciplinary team and family involvement are the foci of the care planning process, which result in a perinatal birth plan that reflects parental values and ethical guidelines.